2019
DOI: 10.1182/blood-2019-01-852392
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and mechanisms of NT5C2-driven chemotherapy resistance in relapsed ALL

Abstract: Mutations in the cytosolic 5′ nucleotidase II (NT5C2) gene drive resistance to thiopurine chemotherapy in relapsed acute lymphoblastic leukemia (ALL). Mechanistically, NT5C2 mutant proteins have increased nucleotidase activity as a result of altered activating and autoregulatory switch-off mechanisms. Leukemias with NT5C2 mutations are chemoresistant to 6-mercaptopurine yet show impaired proliferation and self-renewal. Direct targeting of NT5C2 or inhibition of compensatory pathways active in NT5C2 mutant cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 50 publications
(79 reference statements)
1
37
0
Order By: Relevance
“…6-mercaptopurine (6-MP), a purine base analog commonly used in the treatment of ALL, is incorporated in salvage pathway of purine biosynthesis and induces antitumor effects via inhibition of de novo purine biosynthesis and by inducing apoptosis upon incorporation into DNA (De Abreu 1994). The cytosolic 5 ′ -Nucleotidase II (NT5C2), an enzyme responsible for the intracellular 5 ′ -dephosphorylation of the purine biosynthesis precursors inosine monophosphate (IMP), guanosine monophosphate (GMP), and xanthine monophosphate (XMP), can antagonize the activity of 6-MP by facilitating the dephosphorylation and cellular export of the thiopurine-derived metabolites thio-IMP, thio-XMP, and thio-GMP (Dieck and Ferrando 2019). Notably, somatic activating mutations in NT5C2 are present in 3%-10% of relapsed B-ALL and 20% of relapsed T-ALL cases (Meyer et al 2013;Tzoneva et al 2013;Oshima et al 2016) and can also be found in acute promyelocytic leukemia (APL) relapse samples from patients who have been treated with 6-MP (Lehmann-Che et al 2018).…”
Section: Targeting Nucleotide Biosynthesis and Degradation Pathwaysmentioning
confidence: 99%
“…6-mercaptopurine (6-MP), a purine base analog commonly used in the treatment of ALL, is incorporated in salvage pathway of purine biosynthesis and induces antitumor effects via inhibition of de novo purine biosynthesis and by inducing apoptosis upon incorporation into DNA (De Abreu 1994). The cytosolic 5 ′ -Nucleotidase II (NT5C2), an enzyme responsible for the intracellular 5 ′ -dephosphorylation of the purine biosynthesis precursors inosine monophosphate (IMP), guanosine monophosphate (GMP), and xanthine monophosphate (XMP), can antagonize the activity of 6-MP by facilitating the dephosphorylation and cellular export of the thiopurine-derived metabolites thio-IMP, thio-XMP, and thio-GMP (Dieck and Ferrando 2019). Notably, somatic activating mutations in NT5C2 are present in 3%-10% of relapsed B-ALL and 20% of relapsed T-ALL cases (Meyer et al 2013;Tzoneva et al 2013;Oshima et al 2016) and can also be found in acute promyelocytic leukemia (APL) relapse samples from patients who have been treated with 6-MP (Lehmann-Che et al 2018).…”
Section: Targeting Nucleotide Biosynthesis and Degradation Pathwaysmentioning
confidence: 99%
“…The type III mutations (Q523X) generate a truncated protein due to the loss of the C-terminal tail, impeding a switch toward an inactive protein state [65]. Collectively, these data identify three activating mechanisms by which NT5C2 mutations increase nucleotidase activity, and pave the way for the development of NT5C2 inhibitors to prevent and reverse purine analogue resistance in T-ALL [66].…”
Section: Mechanisms Of Resistance To Standard Chemotherapymentioning
confidence: 99%
“…Incorporation of genetic biomarkers of drugs may lead to better assessment of their efficacy, as demonstrated by previous clinical trials of PARP inhibitors 49 . Importantly, for nucleoside-based anticancer drugs that are structurally similar to antiviral drugs, numerous clinical studies have shown that SNPs and expression status of their relevant transporters and metabolizing enzymes dictated clinical outcome 5054 . Therefore, the transportation, activating and detoxifying mechanisms uncovered in this screen may point to clinical biomarkers of COVID-19 drugs.…”
Section: Discussionmentioning
confidence: 99%